1997
DOI: 10.1038/sj.onc.1200833
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of cyclin E and D1 in breast cancer is associated with inactivation of the retinoblastoma protein

Abstract: Inactivation of the retinoblastoma protein (pRB) by mutations or abnormal phosphorylation is a mechanism by which tumour cells can subdue normal growth control. Among molecules involved in control of pRB phosphorylation, cyclin D1 and E have been found to be deregulated and overexpressed in various types of cancers. In order to study the cell cycle regulatory mechanisms in breast cancer, we have analysed the protein expression of cyclin D1 and E in 114 tumour specimens from patients with primary breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
106
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 41 publications
15
106
1
Order By: Relevance
“…The frequencies of CCND1 amplification (11.2%) and overexpression (33.6%) are in agreement with those previously reported in the literature (Ali et al, 1989;Borg et al, 1991;Schuuring et al, 1992;Henry et al, 1993;McIntosh et al, 1995;Gillett et al, 1996;Barbareschi et al, 1997;Jares et al, 1997;Nielsen et al, 1997;Kenny et al, 1999). Joint analysis of the CCND1 gene at both the mRNA and DNA levels showed that patients with a good outcome had CCND1-unamplified-overexpressed tumours while those with a poor outcome had CCND1-amplified tumours.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The frequencies of CCND1 amplification (11.2%) and overexpression (33.6%) are in agreement with those previously reported in the literature (Ali et al, 1989;Borg et al, 1991;Schuuring et al, 1992;Henry et al, 1993;McIntosh et al, 1995;Gillett et al, 1996;Barbareschi et al, 1997;Jares et al, 1997;Nielsen et al, 1997;Kenny et al, 1999). Joint analysis of the CCND1 gene at both the mRNA and DNA levels showed that patients with a good outcome had CCND1-unamplified-overexpressed tumours while those with a poor outcome had CCND1-amplified tumours.…”
Section: Discussionsupporting
confidence: 89%
“…Clinical studies have found amplification of 11q13 chromosomal region (which contains CCND1) in 10 -15% of human primary breast cancers (Ali et al, 1989;Borg et al, 1991;Schuuring et al, 1992;Henry et al, 1993). However, overexpression (at both the mRNA and protein levels) is seen in about 50% of cases, suggesting that mechanisms other than DNA amplification may dysregulate cyclin D1 expression (McIntosh et al, 1995;Gillett et al, 1996;Barbareschi et al, 1997;Jares et al, 1997;Nielsen et al, 1997;Kenny et al, 1999). It is noteworthy that it has been previously described a high correlation between overexpression of CCND1 mRNA and increased presence of Cyclin D1 protein (Bartkova et al, 1994;Gillett et al, 1994).…”
mentioning
confidence: 99%
“…In this study, we have shown that low levels of cyclin D1 and p27 correlated to poor prognosis in conventional RCC using univariate analysis, and that p27 remained significantly associated to survival in the multivariate analyses. The association between low cyclin D1 and poor prognosis in the univariate analysis agrees with the data reported for breast cancer (Gillet et al, 1996;Nielsen et al, 1997;Hwang et al, 2002;McKay et al, 2002), although an association between high cyclin D1 and poor prognosis has been reported in many malignancies (Å kervall et al, 1997;Gansauge et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Barbareschi et al (22) reported on the expression of pRB, cyclin D1 and p53, but not p16, in 64 breast cancers. Dublin et al (15) and Nielsen et al (38) studied breast tumors (n ϭ 192 and n ϭ 114, respectively) for pRB, cyclin D1 and p16, but not p53 expression. Thus, we believe our series of 77 breast cancers to be the first for which immunohistochemical data on all four major cell cycle regulatory proteins (pRB, p16, cyclin D1, and p53) are available.…”
Section: Discussionmentioning
confidence: 99%